PENGENALAN JENIS MAKER DENGAN METODE COLOR HISTOGRAM DAN EUCLIDEAN DISTANCE - Fattah Wijdjaya Gandhi; Lina Lina (Jurnal Ilmu Komputer dan Sistem Informasi, 2021)
In the midst of the covid-19 virus pandemic the use of masks is increasing to prevent transmission, various types of masks are available among the public but not all types of masks are advised to avoid the transmission of the covid-19 virus. Among them the use of KN-95 masks is recommended to avoid transmission of the virus. This application program uses color histogram and euclidean distance methods to distinguish the types of medical and non-medical masks, the medical masks used in this application program are kn-95 masks that are white. Color histogram is a way to get color dissemination data in photos or images. While euclidean distance is used to get the distance difference between 2 points. A total of 97 photos of medical masks were used as training data, 59 photos of medical masks and 96 photos of non-medical masks were used as test data. The application program recognizes 38 medical masks and 49 non-medical masks, the success rate of this program for recognizing medical and non-medical masks is 58.27%.